NOVEL SIRKUS POHON KARYA ANDREA HIRATA SEBAGAI MATERI AJAR SASTRA: ANALISIS PSIKOLOGI SASTRA DAN NILAI PENDIDIKAN KARAKTER - Sedyaningrum Pujawati; Nugraheni Eko Wardani; Budi Waluyo (Universitas Sebelas Maret, 2019)
The purposes of this research are to describe: (1) structure of novel Sirkus Pohon by Andre Hirata; (2) id, ego, and superego of the main character novel Sirkus Pohon; (3) the value of character education in the novel Sirkus Pohon; and (4) the relevance of novel Sirkus Pohon as material of learning literature in senior high school. This research was conducted by descriptive qualitative method and psychology of literature. The result show that: (1) every elements of novel have in relation to the elements of other to make a story that a solid; (2) each of the characters has the character of different so that make them have balance id, ego, and superego different also; (3) the value of education character contained in the novel covering honest, discipline, hard work, the responsibility, appreciate the achievements, creative, care social, caring environment, and friends; and (4) novel Sirkus Pohon relevant made learning materials if viewed from aspects of the contens, presenting, language, and graph.